2018
DOI: 10.1021/acs.energyfuels.8b02689
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reaction Temperature on the Interpretation of Delplots for the Parallel-Series Reaction Network

Abstract: The use of Delplots to deduce the key features of reaction networks using nonisothermal kinetics data was examined. Using Delplots, a product’s network rank, i.e., the number of reaction steps required for its formation from a specified reactant “A,” is generally obtained by extrapolating plots of yi /x A r vs x A to x A = 0, where at isothermal conditions, contact time was varied to provide the range of conversion supporting the extrapolation. The presently described work addressed the common experimentalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Further efforts were taken to calculate the contributions of primary reactions (based on the Delplot method ) to understand the primary reaction pathways of glucose and fructose decomposition in hot-compressed solvent/water mixtures. Figure compares the contributions of primary reactions during glucose decomposition in hot-compressed solvent/water mixtures at 175 °C.…”
Section: Results and Discussionmentioning
confidence: 72%
“…Further efforts were taken to calculate the contributions of primary reactions (based on the Delplot method ) to understand the primary reaction pathways of glucose and fructose decomposition in hot-compressed solvent/water mixtures. Figure compares the contributions of primary reactions during glucose decomposition in hot-compressed solvent/water mixtures at 175 °C.…”
Section: Results and Discussionmentioning
confidence: 72%
“…Therefore, 5-HMF is indeed a primary product from glucose decomposition under weakly acidic conditions (with an initial pH ≤ 6). However, 5-HMF is not a primary product from glucose decomposition in water (with an initial pH of ∼7), as the intercept of 5-HMF selectivity at glucose conversion X → 0 is zero (see Figure a) according to the Delplot method. There are two possibilities to explain the formation of 5-HMF during glucose hydrothermal decomposition in water: (1) 5-HMF is produced as a secondary product from one of the major primary products (i.e., fructose), and (2) the formation of 5-HMF is catalyzed by organic acids produced during glucose decomposition since 5-HMF is a primary product during glucose decomposition under weakly acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction rate constants of different primary reactions including dehydration, isomerization, and retro-aldol condensation reactions can be estimated by the Delplot method. For example, the reaction rate constant ( k i , min –1 ) of a primary reaction for the product i can be determined using the following equation k i k = lim X 0 nobreak0em.25em⁡ S i = lim X 0 nobreak0em.25em⁡ Y i X …”
Section: Methodsmentioning
confidence: 99%
“…It was found that the presence of species “B” in the feed can make the discernment of the rank of species by the Delplot technique ambiguous because species “B” may appear primary or secondary depending upon the relative magnitude between the ratios of the reaction rate constants of the parallel reactions of species “A” and the feed ratio of “A” to “B”. The effect of using the temperature instead of the isothermal contact time to vary x A was also addressed by Abo-Ghander and Klein for the parallel–series network. It was found that, depending upon the difference between the activation energies of the parallel reaction of species “A” giving species “B” and “D”, species “B” can appear to be primary at a low temperature and non-primary at a high temperature.…”
Section: Introductionmentioning
confidence: 99%